Challenges and Strategies for Pakistan in the Third Wave of COVID-19: A Mini Review - Kamran, Kashif; Ali, Abid (Frontiers in Public Health, 2021)
The world is currently gripped by the fear of the corona virus disease 2019 (COVID-19) pandemic. The causative agent of COVID-19 is a novel coronavirus known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that attacks humans without prejudice, and primarily targets the respiratory system. Pakistan is a developing country with a large population and a weak economy. Currently, it is facing a major challenge to cope with the outbreak of the COVID-19 pandemic, especially the third wave. This fatal virus has increased its presence many folds in Pakistan. On average, 100 deaths per day were being recorded in the late spring of 2021. Delay in the acquisition of vaccine has slowed down the vaccination program for this disease. This in turn will accelerate the spreading of virus, and thus will lead to a lockdown situation.